Ominous choices - Jenkins, Jerry B.; Fabry, Chris, 1961-; LaHaye, Tim F. (Wheaton, Ill. : Tyndale House, 2004)
Trekking to Wisconsin to reunite with Vicki and the others from the Young Tribulation Force, Lionel and Judd are faced with a grim decision when Lionel's arm becomes pinned under a boulder; meanwhile, Vicki struggles to save Cheryl Tifanne's baby.
"The race for life"--Cover.
4.9
5-8
Keywords: Christian life -- Juvenile fiction; Eschatology -- Juvenile fiction; Teenagers -- Juvenile fiction; Christian life -- Fiction; Eschatology -- Fiction; Fantasy; Teenagers -- Fiction; Christian fiction; Christian life -- Fiction; Eschatology -- Fiction; Teenagers -- Fiction; Fantastic fiction; Fantastic fiction; Christian fiction